2018
DOI: 10.1093/jnci/djy015
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Noninferiority Trial of Telephone vs In-Person Disclosure of Germline Cancer Genetic Test Results

Abstract: Even in the era of multigene panel testing, these data suggest that telephone disclosure of cancer genetic test results is as an alternative to in-person disclosure for interested patients after in-person pretest counseling with a genetic counselor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(110 citation statements)
references
References 52 publications
3
105
2
Order By: Relevance
“…These results are consistent with the COGENT study, a multicenter randomized trial of phone compared to in‐person disclosure of germline genetic test results, which included patients undergoing MGPT, the RESPECT study, a study evaluating the uptake and outcomes of returning MGPT research results to research participants, and a recently published study in breast cancer patients focused on cancer worry exclusively . While we found greater increase in uncertainty among patients undergoing MGPT as compared to targeted testing in the COGENT study, longitudinal data from the COGENT study and these data reveal declines in uncertainty over time .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These results are consistent with the COGENT study, a multicenter randomized trial of phone compared to in‐person disclosure of germline genetic test results, which included patients undergoing MGPT, the RESPECT study, a study evaluating the uptake and outcomes of returning MGPT research results to research participants, and a recently published study in breast cancer patients focused on cancer worry exclusively . While we found greater increase in uncertainty among patients undergoing MGPT as compared to targeted testing in the COGENT study, longitudinal data from the COGENT study and these data reveal declines in uncertainty over time .…”
Section: Discussionsupporting
confidence: 86%
“…Equally important, and consistent with the COGENT study, we did not identify increased distress in the short‐term or long‐term among the subset with a positive result. Another subgroup of interest are patients who receive a VUS result, given that approximately 30% of patients who undergo MGPT receive a VUS result, which can be difficult for providers and patients to understand .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Uptake of testing was lower in both studies among those who received pretest counseling by telephone. In the more recent Communication Of GENetic Test Results by Telephone (COGENT) study, including a wider range of cancer genetic testing, including multigene panel testing, we also found that telephone disclosure was noninferior to in‐person disclosure of genetic test results for immediate postdisclosure outcomes …”
Section: Introductionmentioning
confidence: 78%